2023
DOI: 10.1152/physiol.2023.38.s1.5731703
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of passive heat treatment-induced vascular adaptations relative to exercise training

Abstract: Epidemiological data indicate that repeated heat stress improves cardiovascular health, making passive heat therapy (PHT) a potential alternative for those unable to exercise. Few studies to date have examined the potential exercise mimetic effects in humans, and it is unclear how adaptations compare in magnitude to exercise training. OBJECTIVE: To examine the effects of 6 weeks of localized, muscle-focused PHT on resistance artery vascular function, exercise hemodynamics, and exercise performance relative to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Interestingly, Hesketh et al [131] reported that 6 weeks of passive heat stress (via heat chamber at 40°C) induced comparable angiogenesis to time-matched exercise alone (moderate intensity exercise, ~65 % VO 2peak ), albeit in untrained sedentary individuals. Additionally, recent work by Kaluhiokalani et al [132] investigated the impact of 6 weeks of passive heat therapy (via short-wave diathermy) or exercise (knee extension exercise for 2 h, 3 days per week) on vascular function in previously untrained individuals. Blood flow during a passive leg movement increased to the same extent both in the exercise condition (~10.5 %) and heat therapy condition (~8.5 %).…”
Section: Pro-angiogenic Response To Heat Stressmentioning
confidence: 99%
“…Interestingly, Hesketh et al [131] reported that 6 weeks of passive heat stress (via heat chamber at 40°C) induced comparable angiogenesis to time-matched exercise alone (moderate intensity exercise, ~65 % VO 2peak ), albeit in untrained sedentary individuals. Additionally, recent work by Kaluhiokalani et al [132] investigated the impact of 6 weeks of passive heat therapy (via short-wave diathermy) or exercise (knee extension exercise for 2 h, 3 days per week) on vascular function in previously untrained individuals. Blood flow during a passive leg movement increased to the same extent both in the exercise condition (~10.5 %) and heat therapy condition (~8.5 %).…”
Section: Pro-angiogenic Response To Heat Stressmentioning
confidence: 99%